Nyummy Bakery / Afdhal Baharin ... [et al.] - Baharin, Afdhal; Mohammad, Afiq Rahman; Mohd Fuad, Muhammad Faeez Haikhal; Hanis, Muhammad Nabil; Damahuri, Dzarif Nur Haziq (2022)
The Nyummy Bakery is one of the bakeries in universities that offers the suitable price to students for them to buy essential items. The bakery is mainly focuses on becoming a bakery that produces bakery products that uses premium ingredients and utilizes one of a kind recipes that is homemade. The company aims to achieve a high position in the retail bakery industry market based on the concept of student handmade and fresh for oven and brand specialty in the targeted market. The bakery shop offers a wide variety of bakery products. Some of our best sellers are white bread, chocolate chip cookies, and budget cakes. All of the products are certified halal as all of the ingredients that is used are certified halal by JAKIM. So, the product that we sell can be bought by all. Next, the business is led by a strong line up of management team. This team is led by Afdhal bin Baharin who has a small business experience at home and his products sold by his family’s business have become the talk of the town. Then, we have Muhammad Nabil as an administration manager, Dzarif Nur Haziq as marketing manager, Afiq Rahman as an operational manager and Muhammad Faeez Haikhal as financial manager. In addition, the employees hired are all have their experience in accordance with the position set within the company.